2022
DOI: 10.1038/s41598-022-05280-1
|View full text |Cite
|
Sign up to set email alerts
|

Arousal-based pupil modulation is dictated by luminance

Abstract: Pupillometry has become a standard measure for assessing arousal state. However, environmental factors such as luminance, a primary dictator of pupillary responses, often vary across studies. To what degree does luminance interact with arousal-driven pupillary changes? Here, we parametrically assessed luminance-driven pupillary responses across a wide-range of luminances, while concurrently manipulating cognitive arousal using auditory math problems of varying difficulty. At the group-level, our results reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 44 publications
4
18
0
Order By: Relevance
“…Pupil size varies between roughly 2 and 8 mm in diameter (Mathôt, 2018; Pan et al, 2022). For most cognitive-pupillometry experiments, baseline pupil size should not approach these extremes, for the simple reason that maximally constricted or dilated pupils cannot constrict or dilate any further in response to experimental manipulations.…”
Section: Example Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pupil size varies between roughly 2 and 8 mm in diameter (Mathôt, 2018; Pan et al, 2022). For most cognitive-pupillometry experiments, baseline pupil size should not approach these extremes, for the simple reason that maximally constricted or dilated pupils cannot constrict or dilate any further in response to experimental manipulations.…”
Section: Example Experimentsmentioning
confidence: 99%
“…However, within a broad range of baseline pupil sizes, and thus for a broad range of ambient light levels, task-evoked pupil responses are reliably observed (Bradshaw, 1969; Cherng et al, 2020; Pan et al, 2022; Peysakhovich et al, 2017; Reilly et al, 2019; Steinhauer et al, 2004). As a rule of thumb, baseline pupil sizes between 3 and 7 mm are suitable.…”
Section: Example Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the mixed model are reported in the form of effect estimates and its confidence interval in Table 3. [18,22] For this analysis, pupil diameter was considered a dependent variable. Independent factors were age groups (20-39 years; 40-49 years; 50-59 years; and 60-69 years), illuminance condition (scotopic: 0.0 lx; mesopic low: 0.3 lx; mesopic high: 3 lx), refractive error (best sphere: myopes, ≤-0.5 D; emmetropes, ≥-0.25 to ≤+0.50 D; and hyperopes, ≥+0.75 D), and sex.…”
Section: Statistical Modelsmentioning
confidence: 99%
“…[17] It has been found that "effect of cognitive arousal on pupil size interacts multiplicatively with luminance, with the largest effects occurring at low and medium luminance." [18]…”
Section: Study Population and Measurementsmentioning
confidence: 99%